Analisis Kasus-Kasus Kodifikasi Diagnosis Dan Tindakan Medis Di RSUD Pariaman Berdasarkan ICD-10 Dan ICD-9-CM - Ramadona Ganesha (AKADEMI PEREKAM DAN INFORMASI KESEHATAN (APIKES) IRIS PADANG, 2021)
Diagnosis codes and medical procedures need to be given accurately. An accurate code will have an impact on the accuracy of the code grouping report and is related to financing. This research was conducted at Pariaman Hospital to determine the grouping of diagnosis codes and medical procedures based on ICD-10 and ICD-9-CM. Data taken from Pariaman Hospital for the period 01 April – 30 April 2019, namely the number of discharged patients was 649 patients for a total of 30 days and the number of beds was 163. The research method is direct observation of medical record documents. The results obtained were that the highest diagnosis and code based on ICD-10 was a diagnosis of pneumonia with code J18.9 in 32 patients. The highest distribution of patient diagnoses based on bowel movements was BAB XV (Pregnancy, Childbirth and Puerperium) at 21.27% with 140 patients. The most common procedure performed was SC (Sectio Caesarea) with procedure code 74.99 for 8 patients.